The Papers of Thomas A. Edison The Making of an Inventor, February 1847-June 1873 - Jenkins, Reese V. (Johns Hopkins University Press, 1989)
Winner of the Association of American Publishers's Excellence in Professional and Scholarly Publishing, Architecture and Urban Planning AwardThe Making of an Inventor, volume 1 of the monumental The Papers of Thomas A. Edison, takes us through Edison's life from early childhood to age twenty-six, when his work in telegraphy laid the groundwork for some of his best-known inventions. An 1868 telegraph design by the twenty-one-year-old Edison, for instance, reveals the now-familiar drum and stylus that reappeared in the phonograph of 1877 and in his earliest motion picture design. The Making of an Inventor contains 90 percent of all known documents relating to Edison's boyhood and early career, including every entry from his Newark lab notebooks. Illustrated with nearly 600 of the inventor's own drawings and sketches, it provides a comprehensive account of the origins of Edison's creative genius. Praise for previous volumes of The Papers of Thomas A. Edison:"Those interested in America's technological culture can eagerly look forward to the appearance of each volume of the Edison Papers."-Technology and Culture"The essence of the volume is Edison's technical notebooks, a window onto the inventor's workshop. His lucidity comes through everywhere . . . His writing and drawing come together as a single, vigorous thought process."-Russell McCormmach, New York Times."A mine of material . . . Scrupulously edited . . . No one could ask for more . . . A choplicking feast for Edison biographers-well into the next century, and perhaps beyond."-Fred Howard, Washington Post."A triumph of the bookmaker's art, with splendidly arranged illustrations, essential background information, and cautionary reminders of the common sources on which Edison's imagination drew."-David Joravsky, New York Review of Books."In the pages of this volume Edison the man, his work, and his times come alive . . . A delight to browse through or to read carefully."-Thomas J. Misa, Science.